Cover Image, Volume 55, Issue 4. Issue 4 (15th February 2017) - Unknown
Abstract : On page 344 (DOI:10.1002/polb.24279 ), Wai Fen Yong and Tai‐Shung Chung fabricate flexible tough hydrolyzed polymers of intrinsic microporosity (hPIM‐1) films from the PIM‐1 polymer. The effects of PIM‐1 molecular weight, NaOH concentration, hydrolysis temperature and duration on the conversion rate of nitrile groups to carboxylic acid groups, the physicochemical properties of hPIM‐1 films, and their gas transport properties in terms of permeability, solubility coefficient, diffusivity coefficient and fractional free volume (FFV) are discussed.